Improved Immunological Tolerance Following Combination Therapy with CTLA-4/Ig and AAV-Mediated PD-L1/2 Muscle Gene Transfer - Adriouch, Sahil; Franck, Emilie; Drouot, Laurent; Bonneau, Carole; Jolinon, Nelly; Salvetti, Anna; Boyer, Olivier (Frontiers in Microbiology, 2011)
Initially thought as being non-immunogenic, recombinant AAVs (rAAV) have emerged as efficient vector candidates for treating monogenic diseases. It is now clear however that they induce potent immune responses against transgene products which can lead to destruction of transduced cells. Therefore, developing strategies to circumvent these immune responses and facilitate long-term expression of transgenic therapeutic proteins is a main challenge in gene therapy. We evaluated herein a strategy to inhibit the undesirable immune activation that follows muscle gene transfer by administration of CTLA-4/Ig to block the costimulatory signals required early during immune priming and by using gene transfer of PD-1 ligands to inhibit T cell functions at the tissue sites. We provide the proof of principle that this combination immunoregulatory therapy targeting two non–redundant checkpoints of the immune response, i.e. priming and effector functions, can improve persistence of transduced cells in experimental settings where cytotoxic T cells escape initial blockade. Therefore, CTLA-4/Ig plus PD-L1/2 combination therapy represents a candidate approach to circumvent the bottleneck of immune responses directed towards transgene products.